Magic angle effect on adiabatic T1ρ imaging of the Achilles tendon using 3D ultrashort echo time cones trajectory. (19th May 2020) - Wu, Mei; Ma, Yajun; Wan, Lidi; Jerban, Saeed; Jang, Hyungseok; Chang, Eric Y.; Du, Jiang
Abstract : The protons in collagen‐rich musculoskeletal (MSK) tissues such as the Achilles tendon are subject to strong dipolar interactions which are modulated by the term (3cos 2 θ‐1) where θ is the angle between the fiber orientation and the static magnetic field B0 . The purpose of this study was to investigate the magic angle effect in three‐dimensional ultrashort echo time Cones Adiabatic T1ρ (3D UTE Cones‐AdiabT1ρ ) imaging of the Achilles tendon using a clinical 3 T scanner. The magic angle effect was investigated by Cones‐AdiabT1ρ imaging of five cadaveric human Achilles tendon samples at five angular orientations ranging from 0° to 90° relative to the B0 field. Conventional Cones continuous wave T1ρ (Cones‐CW‐T1ρ ) and Cones T2 * (Cones‐T2 *) sequences were also applied for comparison. On average, Cones‐AdiabT1ρ increased 3.6‐fold from 13.6 ± 1.5 ms at 0° to 48.4 ± 5.4 ms at 55°, Cones‐CW‐T1ρ increased 6.1‐fold from 7.0 ± 1.1 ms at 0° to 42.6 ± 5.2 ms at 55°, and Cones‐T2* increased 12.3‐fold from 2.9 ± 0.5 ms at 0° to 35.8 ± 6.4 ms at 55°. Although Cones‐AdiabT1ρ is still subject to significant angular dependence, it shows a much‐reduced magic angle effect compared to Cones‐CW‐T1ρ and Cones‐T2 *, and may be used as a novel and potentially more effective approach for quantitative evaluation of the Achilles tendon and other MSK tissues. Abstract : 3D UTE‐Cones‐AdiabT1ρ shows a much‐reduced magic angle effect.Cones‐AdiabT1ρ increased 3.6‐fold from 13.6 ± 1.5 ms at 0° to 48.4 ± 5.4 ms at 55°, Cones‐CW‐T1ρ increased 6.1‐fold from 7.0 ± 1.1 ms at 0° to 42.6 ± 5.2 ms at 55°, and Cones‐T2* increased 12.3‐fold from 2.9 ± 0.5 ms at 0° to 35.8 ± 6.4 ms at 55°. 3D UTE‐Cones‐AdiabT1ρ may be used as a novel and potentially more effective approach for quantitative evaluation of the Achilles tendon.